From Frame to Environment: Discussing the Development of Lviv during the 1980s (City: History, Culture, Society, 2022)
The paper discusses different perspectives related to the urban development of Lviv during the 1980s and shows the gradual shift from planning urban space to planning urban time and experiences. It focuses on two cases. The first one is connected to the Lviv branch of the Dipromist State Design Institute for Cities, which was responsible for preparing planning documentation for the city and region. It worked with functional zoning and applied the macro-perspective to the space of the city. The second one evolved at the Lviv Polytechnic institute and dealt with the concept of the urban environment. It proposed a human-centered approach to city development and took into account not only the spatial but also the temporal perspective. As an alternative to the dominant discourse and practice of city planning, it remained marginal after the collapse of the USSR. For decades Lviv urban planning continues to rely on the concepts and tools coined in the Soviet planning institutions and leaves human experiences of the city largely outside of the discussion.
Keywords: Lviv; urban planning; frame; environment; 1980s